Relationship between Teacher Educators’ Emotional Intelligence and their Teaching Practices - Maleeha Hammad, Samina Naseem (JCTE, 2023)
The preparation of prospective teachers (PTs) significantly depends on teacher educators. Teacher educators’ responsibility is to teach studentcentered teaching practices to PTs and model those practices in their classrooms. Teachers having higher emotional intelligence (EI) use student-centered teaching practices in their classrooms. Using a descriptive approach, this study focused on two aspects (i) documenting the level of EI of teacher educators and their practices in the Pakistani context, and (ii) finding out the relationship between teacher educators’ EI and their teaching practices. It was hypothesized that teacher educators’ emotional intelligence has no relationship with student-centered practices employed by teacher educators. Teacher educators teaching in B. Ed (Hons.) Elementary programs of Rawalpindi and Islamabad were the population of the study.